Betulin suppresses TNF-α and IL-1β production in osteoarthritis synovial fibroblasts by inhibiting the MEK/ERK/NF-κB pathway. (November 2021) - Su, Chin-Horng; Lin, Chih-Yang; Tsai, Chun-Hao; Lee, Hsiang-Ping; Lo, Lun-Chien; Huang, Wei-Chien; Wu, Yang-Chang; Hsieh, Ching-Liang; Tang, Chih-Hsin
Graphical abstract: Highlights: Upregulation of TNF-α and IL-1β levels in OA tissue. Betulin inhibits TNF-α and IL-1β production in OA disease. The MEK, ERK, and NF-κB signaling pathways mediate the inhibitory effects of betulin in OA inflammation. Abstract: Osteoarthritis (OA) is characterized by the infiltration of a number of proinflammatory cytokines into the joint microenvironment. Betulin is a natural analogue of betulinic acid, a lupane-type pentacyclic triterpene that displays many important biological activities, including anti-inflammatory activity, although the effects on inflammatory cytokine production in OA are unknown. Analyses of samples from the Gene Expression Omnibus (GEO) dataset and our own clinical samples revealed higher levels of tumor necrosis factor alpha (TNF-α) and interleukin 1 beta (IL-1β) in OA synovial tissue compared with normal healthy tissue. This was also the case in synovial tissue from normal healthy rats and rats subjected to anterior cruciate ligament transaction (ACLT)-induced OA. High-throughput screening of inflammatory cytokines in betulin-treated OA synovial fibroblasts (OASFs) identified TNF-α and IL-1β as potential targets of betulin. Further analyses found that betulin suppresses TNF-α and IL-1β production in OASFs by inhibiting mitogen-activated protein kinase (MEK), extracellular signal-regulated kinase (ERK) and nuclear factor kappa B (NF-κB) signaling cascades. Betulin shows promise for the treatment of OA.